Voyages from Montreal Through the Continent of North America to the Frozen and Pacific Oceans in 1789 and 1793. Vol. I - Mackenzie, Alexander, 1764-1820 (Salt Lake City, UT : Project Gutenberg, 2011)
"Voyages from Montreal Through the Continent of North America to the Frozen and Pacific Oceans" by Alexander Mackenzie is a historical account written in the early 19th century. This publication chronicles the author's explorations across North America, detailing his voyages between 1789 and 1793, most notably his pioneering journey to the Pacific Ocean, which was unprecedented for a European at the time. Central to the work is Mackenzie's experiences as a fur trader and explorer, providing insights into the geography, Indigenous populations, and the burgeoning fur trade of the era. The opening of the text introduces Alexander Mackenzie, laying the groundwork for his expeditions and experiences that define the narrative. It provides a biographical sketch, outlining his early involvement in the fur trade and the context that motivated his ambitious voyages. The introduction sets the stage for his accounts of navigating uncharted territories, battling against natural elements, and interacting with Indigenous tribes. As Mackenzie prepares for his travels from Fort Chepewyan, he records his observations, thoughts on the implications of trade, and the socio-economic realities of the fur trade in Canada, all beyond mere geographical exploration, emphasizing the significance of his journeys in expanding commercial landscapes and geographical knowledge. (This is an automatically generated summary.)
Release date is 2011-03-22
Produced by Owen O'Donovan
Keywords: Indians of North America -- Canada; Northwest, Canadian -- Description and travel; Fur trade -- Canada; Indians of North America -- Canada -- Languages -- Glossaries, vocabularies, etc